Philanthropic Epistemology of the Nahdlatul Ulama (NU) Coin Movement in Indonesia - Jauhari, Sofuan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Nadlatul Ulama (NU) is the largest Islamic organization in Indonesia. This organization is known as a traditionalist Islamic group whose members are from rural communities. Even though it is a traditionalist Islamic organization, it turns out that NU has philanthropic activities that have a wide impact through the NU Coin Movement. This article focuses on two questions, namely the function and foundation of the NU Coin Movement. This question is important to answer to find the direction of development of the philanthropic movement carried out by NU. This qualitative research uses literature data related to NU's philanthropic activities, especially the Kon Movement. Data is collected through documentation. After verification, the data is analyzed and conclusions are drawn using the interactive cycle pattern developed by Miles and Huberman. This research concludes two things.First,The Nahdlatul Ulama (NU) coin movement functions as a means of channeling an attitude of generosity to its followers, who on average belong to the lower middle economic community in Indonesia. Second, the Nahdlatul Ulama (NU) coin movement is based on three foundations at once, namely religious, philosophical and socio-cultural foundations